Some Observations on Student Values and Their Implications for Accounting Education. - Brenner, Vincent C. (The Accounting Review, 1973)
Abstract This article focuses on the attitude of business students towards social problems. This paper reports comparisons which were made of entering freshmen who have elected a field of business at Virginia Tech with the national average for all curriculums. Of the business students 97.9% believed that the Federal government should do more about pollution, but this percentage was below the national average. Overall, the data indicated that entering business students seem to be strongly concerned about our social and economic problems. Accounting students were found to have positive attitudes toward parents, people in general, and authority, whereas creative writing students displayed negative attitudes. On the basis of this and other research, it seems logical to infer that accounting students are deeply concerned with social and economic problems. The challenge for accounting educators is to promote student interest in social and economic affairs and to assist the student in implementing his skills in a constructive manner toward a solution to these problems.